The Effectiveness of Combination Toothbrushing Techniques on Oral Hygiene Index (PHP-M) in Pre-School Children at Harapan Indah Kindergarten, Pontianak: Efektifitas Teknik Menyikat Gigi Kombinasi Terhadap Indeks Kebersihan Mulut (PHP-M) Pada Anak Pra-Sekolah Di TK Harapan Indah Pontianak - Syarifah Lia Rismana; Neny Setiawaty Ningsih; Fathiah Fathiah; Halimah Halimah (Poltekkes Kemenkes Kupang, 2020)
The combination tooth brushing technique is the technique most often taught in dental health education. Given the importance of maintaining dental and oral hygiene for pre-school children, parents play an important role in taking preventive measures, namely by brushing teeth twice a day, in the morning after breakfast and at night before going to bed using a combination technique that is often recommended in dental health education. and mouth. The purpose of this study was to analyze the effectiveness of the combined tooth brushing technique on changes in the oral hygiene index (PHP-M) of pre-school children at Harapan Indah Kindergarten, Pontianak. This research method is a quasi-experimental (quasi-experimental) with the research design used in this study is the One Group Pre-test-Post-test Design. In this design, a pre-test was carried out to determine the initial state of the subject before being treated so that the researcher could find out the condition of the subject being studied before or after being given treatment whose results can be compared or seen changes, with a total of 31 respondents aged 6 years. The test results obtained that the mean/average of the initial PHP-M index before brushing with individual techniques was 46.61 and the mean/average of the final PHP-M index after brushing with individual techniques was 33.12 with a mean difference of 13.49, while the mean/average index of the initial PHP-M before brushing the teeth with the combination technique was 45.74 and the mean/average of the final PHP-M index after brushing the teeth with the combination technique was 19.64 with a mean difference of 26.1, with the probability after brushing teeth with individual and combination techniques is 0.000 because the probability is less than 0.05 then accept Ha, which means there is a significant difference before and after brushing teeth with the combination technique. Based on the research conducted, it is concluded that the combined tooth brushing technique is more effective in reducing the PHP-M index compared to the individual tooth brushing technique. Teknik menyikat gigi kombinasi adalah teknik yang paling sering diajarkan dalam penyuluhan kesehatan gigi. Mengingat begitu pentingnya menjaga kebersihan gigi dan mulut anak pra-sekolah, maka dari itu orang tua berperan penting dalam melakukan tindakan pencegahan yaitu dengan menyikat gigi dua kali sehari, pagi setelah sarapan dan malam sebelum tidur dengan menggunakan teknik kombinasi yang sering dianjurkan dalam penyuluhan kesehatan gigi dan mulut. Tujuan penelitian ini adalah untuk menganalisis efektifitas teknik menyikat gigi kombinasi terhadap perubahan indeks kebersihan mulut (PHP-M) anak pra sekolah di TK Harapan Indah Pontianak. Metode penelitian ini adalah eksperimental quasi (semu) dengan desain penelitian yang digunakan dalam penelitian ini adalah One Group Pretest-Posttest Design. Pada desain ini dilakukan pre-tes untuk mengetahui keadaan awal subjek sebelum diberi perlakuan sehingga peneliti dapat mengetahui kondisi subjek yang diteliti sebelum atau sesudah diberi perlakuan yang hasilnya dapat dibandingkan atau dilihat perubahannya, dengan jumlah 31 responden yang berumur 6 tahun. Hasil uji diperoleh mean/rata-rata indeks PHP-M awal sebelum menyikat gigi dengan teknik individual adalah 46,61 dan mean/rata-rata indeks PHP-M akhir setelah menyikat gigi dengan teknik individual adalah 33,12 dengan selisih mean 13,49, sedangkan mean/rata-rata indeks PHP-M awal sebelum menyikat gigi dengan teknik kombinasi 45,74 dan mean/rata-rata indeks PHP-M akhir setelah menyikat gigi dengan teknik kombinasi adalah 19,64 dengan selisih mean 26,1, dengan probabilitas setelah menyikat gigi dengan teknik individual dan kombinasi 0,000 karena probabilitasnya lebih kecil dari 0,05 maka menerima Ha yang artinya ada perbedaan yang signifikan sebelum dan sesudah menyikat gigi dengan teknik kombinasi. Berdasarkan penelitian yang dilakukan, maka disimpulkan bahwa teknik menyikat gigi kombinasi lebih efektif dalam menurunkan indeks PHP-M dibandingkan dengan teknik menyikat gigi individual.